A coupling model for amplified spontaneous emission in laser resonators. (24th August 2015) - Su, Hua; Wang, Xiaojun; Shang, Jianli; Yu, Yi; Tang, Chun
Abstract: The competition between amplified spontaneous emission (ASE) and main laser in solid-state laser resonators is investigated both theoretically and experimentally. A coupled model using the spatial volume integral instead of the Monte Carlo type raytrace technique is proposed to depict ASE in the laser resonators. This model is able to evaluate all possible reflections at both the polishing surface and the diffusive side, to calculate ASE for an inhomogeneous gain distribution, and to include the spectral correction. An experiment is carefully designed to verify the theoretical model and to investigate the distinct physical properties caused by the coupling between ASE and the laser oscillations. The experimental data exhibit an excellent agreement with the theoretical predictions. According to that model, we confirm that ASE in thin-disk lasers can be characterized approximately by the product of the threshold gain of the resonator and the diameter of the disks, as laser modes are highly overlapped with the pumping beam. Theoretical evaluation shows that the scattering characteristic of the disk side impacts on ASE significantly. Furthermore, we point out that ASE decreases output laser power by affecting threshold pumping power, while slope efficiency is not changed by ASE. This observation provides us with a simple way to estimate the decrease of the optical efficiency by ASE.